2020
DOI: 10.1542/peds.2019-0629
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Support for Infants With Genetic Disorders

Abstract: As the technical ability for genetic diagnosis continues to improve, an increasing number of diagnoses are made in infancy or as early as the neonatal period. Many of these diagnoses are known to be associated with developmental delay and intellectual disability, features that would not be clinically detectable at the time of diagnosis. Others may be associated with cognitive impairment, but the incidence and severity are yet to be fully described. These neonates and infants with genetic diagnoses therefore re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…For many, a genetic diagnosis can be life changing, even in the absence of a therapeutic option (Lingen et al, 2016). Following diagnosis, quality of life is often improved by participation in support groups that can provide longitudinal prognostic information, genetic counseling, and informed reproductive decisions with opportunities for preimplantation genetic diagnosis or prenatal testing particularly in the case of inherited variants where there is a sizable recurrence risk (Sexton et al, 2008;Wojcik et al, 2020).…”
Section: Clinical Impact Of Novel Mendelian Conditionsmentioning
confidence: 99%
“…For many, a genetic diagnosis can be life changing, even in the absence of a therapeutic option (Lingen et al, 2016). Following diagnosis, quality of life is often improved by participation in support groups that can provide longitudinal prognostic information, genetic counseling, and informed reproductive decisions with opportunities for preimplantation genetic diagnosis or prenatal testing particularly in the case of inherited variants where there is a sizable recurrence risk (Sexton et al, 2008;Wojcik et al, 2020).…”
Section: Clinical Impact Of Novel Mendelian Conditionsmentioning
confidence: 99%
“…Rarely, there are effective treatments available such as the ketogenic diet for glucose transporter 1 deficiency syndrome (Klepper et al, 2020). While none of the supportive treatments available are curative for most NDDs, early intervention has been demonstrated to improve outcomes for Down Syndrome and other NDDs (Fidler et al, 2021;Guralnick, 2010Guralnick, , 2011Pinero-Pinto et al, 2020;Wojcik et al, 2020). Furthermore, in the conceptual framework established with SMA, the concurrent pilot NBS study and clinical trial with nusinersen were structured to co-evolve, enabling early identification of newborns during a critical therapeutic window in which treatments were most efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…EIP includes services and supports available to young children with developmental delays and disabilities by teaching them through additional support and repetition how to best adapt with their limitations and use their relative strengths. It has been shown to improve outcomes and minimize the burden of associated behavioral conditions including autism (Bonnier, 2008; Purpura et al, 2014; Wojcik, Stewart, Waisbren, & Litt, 2020). In a randomized clinical trial in infants age 9–14 months showing early behavioral signs of autism, EIP demonstrated reduced autism symptom severity and reduced likelihood of an eventual autism diagnosis (Whitehouse et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Third, our study is limited by the focus on preterm infants. While this is an important population, the high-risk infant population requiring specialized follow up also includes infants with hypoxic-ischemic encephalopathy, genetic disorders 38 and those requiring surgery. 39 …”
Section: Discussionmentioning
confidence: 99%